Penggunaan Metode STAR untuk Memahami Materi Tafakur (Q.S. Al Ikhlas Ayat 1) : Kajian Literatur dalam Konteks Mata Pelajaran Religi, PKn, IPA, dan Matematika - Syamsuhari; M. Hamim Thohari; Sambang Pangesthi; Putri Dwi Naryaningsih (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2024)
This research aims to explore the application of STAR (Situation, Task, Action, Reflection) methods in various subjects to understand the tafakur material related to Surah Al-Ikhlas verse 1. STAR methods are applied in Religious Education, Citizenship Education (PKn), Natural Sciences (IPA), and Mathematics to deepen the understanding of the unity of God and its relevance in an academic context. The research uses literature study approaches and qualitative analysis to dig out how STAR methods can be integrated into each subject. The results show that STAR method is effective in helping students understand tauhid teachings in a structured and relevant way. In IPA, the STAR method explores the function of body organs related to speaking about the unity of God, and in Mathematics, this method shows the relevance of the concept of unity in the calculation of numbers. Reflection is done to evaluate the effectiveness of teaching and improve student learning outcomes. This study concludes that the STAR method can be applied effectively to improve understanding and internalization of tafakur teachings in various educational contexts.